Influence of Temperature and Growth Phase on Expression of a 104-Kilodalton Listeria Adhesion Protein in Listeria monocytogenes - Santiago, Nivia I. (American Society for Microbiology (ASM), 1999)
Interaction of Listeria monocytogenes with mammalian intestinal cells is believed to be an important first step in Listeria pathogenesis. Transposon (Tn916) mutagenesis provided strong evidence that a 104-kDa surface protein, designated the Listeria adhesion protein (LAP), was involved in adherence of L. monocytogenes to a human enterocyte-like Caco-2 cell line (V. Pandiripally, D. Westbrook, G. Sunki, and A. Bhunia, J. Med. Microbiol. 48:117–124, 1999). In this study, expression of LAP in L. monocytogenes at various growth temperatures (25, 37, and 42°C) and in various growth phases was determined by performing an enzyme-linked immunoassay (ELISA) and Western blotting with a specific monoclonal antibody (monoclonal antibody H7). The ELISA and Western blot results indicated that there was a significant increase in LAP expression over time only at 37 and 42°C and that the level of LAP expression was low during the exponential phase and high during the stationary phase. In contrast, there were not significant differences in LAP expression between the exponential and stationary phases at 25°C. Examination of the adhesion of L. monocytogenes cells from exponential-phase (12-h) or stationary-phase (24-h) cultures grown at 37°C to Caco-2 cells revealed that there were not significant differences in adhesion. Although expression of L. monocytogenes LAP was different at different growth temperatures and in different growth phases, enhanced expression did not result in increased adhesion, possibly because only a few LAP molecules were sufficient to initiate binding to Caco-2 cells.